Evaluation of Proton Therapy Dose Depth Using Passive Scattering Technique with Range Modulated Wheel (RMW) On Water Phantom Using PHITS Version 3.34 - Hilda S. Putri; Pandji Triadyaksa; Heri Sutanto; Fajar Arianto; Nisfi D. Fauziah; Sarah I. Izmi; Revita Dewantari; Pingki S. Dewi; Rio A.G. Fernando (International Journal of Scientific Research in Science and Technology, 2025)
Proton therapy is a modality of radiotherapy that has a Bragg peak that can provide the correct radiation dose to cancer cells and minimize the dose to healthy tissue. In proton therapy, there is a passive scattering technique with a Range Modulated Wheel (RMW) in the form of a rotating wheel that scatters and compensates for the scattering effect. RMW has several steps, including lead and lexan. This study evaluated the depth of proton therapy dose on water phantom using passive scattering with various RMW steps. The study was conducted by simulation using the PHITS Version 3.34 program. The geometry of the passive scattering nozzle and water phantom was simulated by entering RMW step data to obtain the dose depth. Based on the simulation results in step 1, the thickness of the lexan was thinner, resulting in a more extended dose range and higher dose. In contrast, in step 6, the thickness of the lexan was increased, resulting in higher scattering, which could reduce the dose and depth range.
Keywords: Lead; Lexan; Range Modulated Wheel; Passive Scattering; PHITS